2014
DOI: 10.5152/dir.2014.13415
|View full text |Cite
|
Sign up to set email alerts
|

Development, growth, propagation, and angiographic utilization of the rabbit VX2 model of liver cancer: a pictorial primer and “how to” guide

Abstract: The VX2 tumor is a leporine anaplastic squamous cell carcinoma characterized by rapid growth, hypervascularity, and facile propagation in the skeletal muscle. Since its introduction over 70 years ago, it has been used to model a variety of malignancies, and is commonly employed by interventional radiologists in preclinical investigations of hepatocellular carcinoma. However, despite the widespread and lasting popularity of the model, there are few technical resources detailing its use. Herein, we present a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 27 publications
0
34
0
7
Order By: Relevance
“…The VX2 line is quite cumbersome to use, as a culture protocol has not been established and the cells have to be propagated as muscle implants into syngeneic (New Zealand White) rabbits. Tumors are then dissected and implanted into syngeneic recipient target organs [19]. VX2 is characterized by very rapid, aggressive growth and hypervascularity, but with a high rate of spontaneous necrosis of tumor cells [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VX2 line is quite cumbersome to use, as a culture protocol has not been established and the cells have to be propagated as muscle implants into syngeneic (New Zealand White) rabbits. Tumors are then dissected and implanted into syngeneic recipient target organs [19]. VX2 is characterized by very rapid, aggressive growth and hypervascularity, but with a high rate of spontaneous necrosis of tumor cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors are then dissected and implanted into syngeneic recipient target organs [19]. VX2 is characterized by very rapid, aggressive growth and hypervascularity, but with a high rate of spontaneous necrosis of tumor cells [19]. Although it has been suggested that there are similarities between glioma and VX2, the clinical relevance of VX2 as a primary brain tumor model is limited, and should be rather considered as a model of brain metastatic tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, skin preparation and an incision of 4–5 cm were made on the right hind limb until reaching the surrounding tumor area. Two curvilinear incisions were made within the muscle, in order to remove the tumor mass en-bloc as described in Parvivian et al[16]. The explanted tumor was bisected in order to detect any gross evidence of a necrotic core to obtain viable peripheral tumor.…”
Section: Methodsmentioning
confidence: 99%
“…It is of note that this model has been used to model various types of cancer, including those of pancreas, kidney and liver [5–15]. The transplantation of VX2 cells can be achieved either by implanting solid tumor pieces or by injecting the tumor cell suspensions (fresh or frozen) as previously described [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Преимущественно используется опухоль VX2 (плоскоклеточная карцинома). Перевивку этой опухоли применяют в экспериментальной онкологии для моделирования злокачественных новообразований головы и шеи, почки, головного мозга, печени [62], при исследовании колоректального рака с метастазами в печень [67]. Для исследования образования метастазов лимфатическая система кролика подходит больше, чем у грызунов [61].…”
Section: трансгенные и нокаутные кролики в биомедицинеunclassified